Performance, Carcass Characteristics and Blood Composition of Broilers Fed Varying Levels of Palm Kernel Meal (Elaise guinensis) Supplemented with Different Levels of Fishmeal - Khadijat , Bello M.; Enoch, Oyawoye O.; Suleiman, Bogoro E. (International Journal of Poultry Science, 2011)
An experiment was conducted to evaluate the performance, carcass characteristic and blood composition of broilers fed palm kernel meal based diet supplemented with two levels of fish meal. Two hundred and ten (210) day old Anak broiler chicks were randomly allocated to seven dietary treatments in which PKM was used at graded levels to replace maize and Groundnut Cake (GNC) in the diets. The diets were supplemented with either low (2%) or high (5%) levels of fish meal. The results of the performance parameters showed a significant treatment effect. The daily feed intake showed a significant increase with PKM inclusion level up to 30% but declined thereafter. The daily weight gains recorded were better at all levels compared to the control. The feed conversion ratio similarly increased with increase in PKM inclusion levels, just as feed intake and weight gain also increased with FM inclusion level. However, the FCR decreased with increasing levels of fishmeal. The feed cost/kg tended to decrease with increasing PKM levels but increased with an increase FM levels. However the feed cost/kg weight gain increased as the level of PKM was increased. The blood constituents of the broilers were not affected by dietary levels of PKM and FM except for the urea (p<0.05). Though, there was no definite pattern. The carcass analysis was also not affected by PKM and FM inclusion levels except for the plucked weight which was lower at 5% FM level. The result indicated that PKM can be included at 45% in a corn- groundnut cake diet supplemented with 5% fish meal without detrimental effects on performance, carcass yield and blood composition of broilers. However, 30% seems to be most economical.